Design and analysis of a pulsed electromagnetic blankholder system for electromagnetic forming. (2017) - Huang, Yujie; Han, Xiaotao; Cao, Quanliang; Lai, Zhipeng; Cai, Hong; Liu, Ning; Li, Xiaoxiang; Chen, Meng; Li, Liang
Abstract: A pulsed electromagnetic blankholder system consisting of a pulsed magnet driven by a capacitor bank and a conductive ring as a blank holder has been proposed, designed, and analyzed for electromagnetic forming. The blank holder force (BHF) supplied by the system is a huge repulsive electromagnetic force generated in the blank holder by the interaction between the pulsed magnetic field and the induced eddy current. The electromagnetic performance of the system has been investigated in detail based on finite element method, and simulation results show that the system can generate a pulsed BHF ranging from 0 to 1000 kN at different discharge voltages with a rise time of more than 5 ms, which fulfills the common requirements for electromagnetic forming process.